PERBANDINGAN TEKNIK BUDIDAYA TANAMAN KELAPA SAWIT (Elaeis guineensis Jacq) POLA KKPA DI KABUPATEN ROKAN HILIR DAN KABUPATEN SIAK DENGAN PT. MINAMAS PLANTATION - A. Muchlis '; Adiwirman ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
This subject aims to study and compare the execution of oil palm (Elaeis guineensis Jacq) cultivation techniques KKPA pattern in Rokan Hilir and Siak Riau province with oil palm cultivation techniques standards issued or recommended by the oil palm plantation company PT. Minamas Plantation. The research was conducted in the oil palm plantation crop yield KKPA pattern in Rantau Bais, Tanah Putih, Rokan Hilir and Kotoringin Village, District Mempura, Siak. This research was carried out for 2 months, beginning in August 2014 to September 2014. This study used survey method. The information employed in this study are primary data and secondary information. The information obtained in Rokan Hilir and Siak then analyzed descriptively. In this study the number of samples taken is 10% of the entire population. Parameters investigated in cultivation techniques, namely the extraction of seeds, land clearing, planting distance, spacing of the form, the size of the planting hole, replanting, fertilization, prunning, weed control and output. Farmers in the district by 60.24% Rokan Hilir who follow the advice of PT. Minamas Plantation and the Directorate General of Plantation in Fauzi et al, while 80.50% of farmers in Siak follow the advice. Farmers samples in Rohil only a fraction (19.03%) following fertilization 5T conceptualized while the sample farmers in Siak 51.90%. So this will affect the production of oil palm plantations. Based on the data that has been provided by the cooperative in each district that results TBS farmers in Rohil                     of 747.6 kg/ha/month, while the results of TBS farmers in Siak of                  1126.7 kg/ha/month.   Keyword: KKPA, Palm Oil, Rokan Hilir District and Siak District